ANALISIS PERBEDAAN PERILAKU KONTRAPRODUKTIF TENAGA KEPENDIDIKAN BERDASARKAN GENDER DAN USIA - Ice Kamela; Antoni Antoni (Ensiklopedia Social Review, 2020)
This study aims to analyze differences in counterproductive behavior of education personnel based on gender and age in Private Universities in the City of Padang. The data used in this research are prmer and secondary data. Research data collection using a questionnaire. The analytical method used in this research is the Independent Sample T test and Annova test. The sample used was 100 education personnel at Bung Hatta University and Baiturrahmah University. The results of the Independent Sample T Test analysis showed that there was no difference in counterproductive behavior of education personnel based on gender and there was no difference in counterproductive behavior of education personnel based on age.